PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA ADABIAH PADANG - Nurvatjri, Neza; Anggraini, Villia; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of this research isÂ students comprehension of mathematical concepts is low and the lack of cooperation of students with other students. The aims of this study is to determine whether students comprehension of mathematical concepts by using cooperative learning Make a Match a better comprehension of mathematical concepts than students using the conventional teaching high school students of class XI Science Adabiah Padang Academic Year 2013/2014. Experimental research is type of this research, with a random design on the subject. Sampling was done randomly, which was selected as the experimental class is a class XI IPA2 and class XI IPA1 as the control class. The research instrument is the final test of learning that contains an indicator of comprehension the concept of the reliability of the test is Â = 0.93. Based on the analysis of data got by the average value of the experimental class higher than the control class. Hypothesis testing using the Mann-WhitneyÂ test. From the calculation of z â¤ -1.9158 has a probability under H0 of p = 0.0274; because it is smaller than Î± = 0.05, reject H0 and accept H1 , so Â the hypothesis is accepted. Based on the hypothesis test results concluded that the students comprehension of mathematical concepts that apply cooperative learning Make a Match a better than comprehension of mathematical concepts than students with applying conventional learning.